Adat Court in Aceh, Indonesia: a Review of Law - Mansur, Teuku Muttaqin; Sulaiman, Sulaiman; Ali, Hasbi (SCAD Independent, 2020)
This article aims to find out the legal position, authority, and structure of adat(customary) court in Aceh. This study used juridical methods. Data were obtained through literacy studies by examining such as the rule of laws, books, and journals. Data were analyzed using a qualitative descriptive approach. The results of the study showed that adat court in Aceh has a significant position in the legislative system. The authority of the adat court in Aceh is able to resolve small disputes that occur in society. The structure of adat court in Aceh is divided into land and sea areas. Adat court in the land territory consists of the village and the mukim adat court, and the sea territory consists of lhok and district adat court.